Regular meta-analysis of the impact of sports activities intervention on some items of the national student physical health standards for adolescents - Sun, Jikun; Sun, Zhiyuan; Kong, Jianda; Tian, Xuewen; Wang, Liping; Wang, Qinglu; Xu, Jun (Frontiers in Physiology, 2024)
Background: By using meta-analysis to evaluate the effects of exercise on adolescent body mass index (BMI), standing long jump, sit ups, lung capacity, sitting forward bending, 50 meter running, and 800 meter running, a large amount of literature will be reviewed to reveal the key role of exercise in the healthy development of adolescents. This study aims to promote the development of adolescent physical health and solve the common problem of declining physical fitness, comprehensively improve the physical fitness of adolescents, and provide decision-making support for policy makers. The research results will provide methodological references for precise and effective intervention practices, further improve adolescent physical fitness, and lay a solid physiological foundation for their comprehensive development.A literature search was conducted on China National Knowledge Infrastructure (CNKI) and PubMed, collecting randomized controlled trials (RCTs) that investigated the effects of physical activity on adolescent physical fitness according to predefined criteria. The quality of these studies was assessed, and their outcome data were analyzed using RevMan 5.4 software. The analysis encompassed 13 articles with a total of 4,633 participants, examining measures such as mean difference (MD) and heterogeneity, followed by subgroup analyses.The meta-analysis revealed that physical activity had a moderate to high effect on adolescent performance in sit-ups (MD = 4.91, 95% CI = 3.41 to 6.41), vital capacity (MD = 120.66, 95% CI = 48.67 to 194.46), sit-and-reach test (MD = 0.82, 95% CI = 0.09 to 1.56), 50-meter dash (MD = -1.05, 95% CI = -1.48 to -0.62), and 800-meter run (MD = -18.48, 95% CI = -24.98 to -11.97). Conversely, its